ANALISIS PENGGUNAAN SMARTPHONE PADA SISWA KELAS XI IPS 3 DI SMA NEGERI 15 MEDAN SUNGGAL - Rina Suryani; Rosihandayani Rosihandayani; Nirma Fiana; Sri Rizki (Jurnal Mahasiswa BK An-Nur : Berbeda, Bermakna, Mulia, 2023)
Smartphone is a cellular phone that uses several services such as a screen, microprocessor, memory, and built-in modem. Where the presence of this smartphone provides benefits and convenience to its users, especially for students, various impacts are found both in positive and negative terms from the use of existing smartphones. This research uses descriptive kuantitative research methods because in its implementation it includes data, analysis and interpretation of the meaning of the data obtained. The aim of this research is to find out the number of smartphones used by each student, the intensity of smartphone use among students, the applications used on smartphones, the purpose of students using smartphones and the impact of smartphone use on students. Based on the results of research conducted in class XI IPS 3, all students in the class have personal smartphones, and it is known that the majority of male and female students have a smartphone with a total of one, and there is only one male student who has more than one smartphone in class. XI IPS 3. In Conclusions regarding the intensity of smartphone use of students in this class are in the high user category, namely around 4 hours, the application that students often use is WhatsApp, the purpose of students using smartphones is to search for information and the impact felt by students when playing with smartphones is mostly sore eyes.